PENCEGAHAN KECANDUAN ALKOHOL PADA REMAJA MELALUI LAYANAN BIMBINGAN KELOMPOK BERBASIS TEKNIKSELF-MANAGEMENT - M Fadhli Aviv; Kusnadi; Zhila Jannati (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
In helping to change the behavior of adolescents addicted to alcohol, they need mentors who guide them to get away from alcohol, switch to a good path, leave the conduct of intoxicating drinks, and focus on achieving the future. This thesis is entitled "Prevention of Alcohol Addiction in Adolescents Using Group Guidance Services Based on Self-Management Techniques." In this study, researchers have a goal to help adolescents who are addicted to alcohol so that they can return to the right path. They can continue to develop their talents and interests and be able to make their parents or other family members happy. This study uses a qualitative approach, namely research conducted by explaining, describing, and describing the main issues to be discussed in this study, then concluding deductively. The subjects of this study were teenagers in Jati Rahayu Barat Village, Martapura District, OKU Timur Regency. Based on the survey results, thank God, adolescents addicted to alcohol have changed a lot, although they have not entirely changed. This approach uses self-management techniques and group guidance services. This approach is carried out individually or in groups to help adolescents solve their problems independently. By applying self-management techniques and group guidance services, besides experiencing physical and psychological changes, adolescents also become more enthusiastic and motivated to achieve their goals, erasing all the bad memories that have been carried out so far. Self-management techniques are a form of therapy for adolescents addicted to alcohol. Some have promised not to do anything wrong for them, namely getting drunk and drinking alcoholic beverages to the point of addiction.